Exposição ocupacional e a atividade metabólica de trabalhadores durante a aplicação de produtos fitossanitários na cultura do cafeeiro - RAMIRIO, Lucas Deleon (2019)
During the application of phytosanitary products in coffee trees, workers may be exposed to temperatures that could compromise their health. Exposure to occupational heat can lead to progressive dehydration, cramps, exhaustion and the possibility of thermal shock. In this way, knowing the levels of occupational heat that workers are exposed becomes important. The present study aimed to evaluate the occupational exposure to heat of workers during the application of phytosanitary products with manual costal pump in the coffee crop. The case study was developed at the IFSULDEMINAS - Campus Inconfidentes school farm in the months of September and October 2017. Occupational heat in coffee plants was evaluated using the IBUTGMÉDIO method, using TGD 400 thermal stress meter. The IBUTG values found were compared to the exposure limits of NR 15 for the purpose of classification of unhealthy and NHO 06 for acclimatized and non acclimatized workers. The results showed that the IBUTG found is below the tolerance limit of NR15, for the month of September. In October, the tolerance limit was exceeded in the period from 11:00 am to 2:59 pm, considering a continuous heavy activity and rest in the workplace, being considered unhealthy activity. When considering the criteria of the NHO 06 it was observed that the limits of occupational exposure were exceeded in the month of October, for acclimatized and non acclimatized workers. In September the occupational exposure limit of NHO 06 was exceeded only for non acclimated workers. Therefore, the workers should be submitted to acclimatization during the phytosanitary application activity in the month of October.